Firm Competitive Advantage Through Relationship Management A Theory for Successful Sustainable Growth - Deszczyński, Bartosz (Springer Nature, 2021)
Relationship management (RM) is an essential part of business, but its success as a business model can be hard to measure, with some firms embracing a model that is truly relationship-orientated, while others claim to be relationship-orientated but in fact prefer transactional short-term gain. This open access book aims to develop a mid-range theory of relationship management, examining truly relationship-orientated firms to discover not only what qualities these firms have that make them successful at the RM model, but also what benefits this model has for the firm. It addresses questions like how RM-mature companies achieve and sustain competitive advantage, and what determines the scale and scope of these firms, illustrating with case studies. This book will be of interest to scholars studying leadership and strategy, especially those interested in relationship management, business ethics and corporate social responsibility. It will also be of interest to professionals looking to develop their understanding of relationship management.